Which statement is true about the product (9x2 – 4y2)(3x – 2y)?
1 answer:
Answer:
It's the last choice.
Step-by-step explanation:
1. (3x - 2y)(3x -2y)
= 9x^2 - 12xy + 4y^2
The product is (9x^2 - 4y^2) (9x^2 - 12xy + 4y^2)
which is neither a difference of 2 squares or perfect square trinomial.
2. (3x - 2y)(3x + 2y)
= 9x^2 - 6xy + 6xy - 4y^2
= 9x^2 - 4y^2
and (9x^2 - 4y^2(9x^2 - 4y^2) is a perfect square.
You might be interested in
Answer:
5/6 or 4/6
Step-by-step explanation:
6-2=
4/6 -with out two
5/6 -including two
Answer:
65%
Step-by-step explanation:
Answer:
37.5 Miles Per Gallon
Step-by-step explanation:
You find the unit rate of miles per gallon by dividing the miles by the gallons
356.25/9.5
= 37.5
1. 17 + (-9) = 8
2. (-6)+ 12= 6